ALMA uncovers highly filamentary structure toward the Sgr E region - Wallace, Jennifer; Battersby, C.; Mills, E. A. C.; Henshaw, J. D.; Sormani, Mattia C.; Ginsburg, A.; Barnes, A. T.; Hatchfield, H. P.; Glover, Simon; Anderson, L. D. (The astrophysical journal, 2022)
We report on the discovery of linear filaments observed in the CO(1-0) emission for a ∼2′ field of view toward the Sgr E star-forming region, centered at (l, b) = (358.°720, 0.°011). The Sgr E region is thought to be at the turbulent intersection of the “far dust lane” associated with the Galactic bar and the Central Molecular Zone (CMZ). This region is subject to strong accelerations, which are generally thought to inhibit star formation, yet Sgr E contains a large number of H ii regions. We present 12CO(1-0), 13CO(1-0), and C18O(1-0) spectral line observations from the Atacama Large Millimeter/submillimeter Array and provide measurements of the physical and kinematic properties for two of the brightest filaments. These filaments have widths (FWHMs) of ∼0.1 pc and are oriented nearly parallel to the Galactic plane, with angles from the Galactic plane of ∼2°. The filaments are elongated, with lower-limit aspect ratios of ∼5:1. For both filaments, we detect two distinct velocity components that are separated by about 15 km s−1. In the C18O spectral line data, with ∼0.09 pc spatial resolution, we find that these velocity components have relatively narrow (∼1-2 km s−1) FWHM line widths when compared to other sources toward the Galactic center. The properties of these filaments suggest that the gas in the Sgr E complex is being “stretched,” as it is rapidly accelerated by the gravitational field of the Galactic bar while falling toward the CMZ, a result that could provide insights into the extreme environment surrounding this region and the large-scale processes that fuel this environment.
Gesehen am 14.02.2023